Flight software development of SCOOBI CubeSat - Yeo, Marcus Rui Han (2019)
A CubeSat is a Nano-satellite, measuring between 1 to 12 U, 1U being 10x10x10cm adopted as a CubeSat size unit. The CubeSat-class of Satellites has a myriad of uses in the space industry, from providing a cost-effective platform for academic research institutions to delve into amateur-professional grade space missions as well as commercial uses in primary use-cases such as telecommunications services [1]. The component design of the CubeSat is characterised into multiple different subsystems: the communication subsystem, the power subsystem, the onboard computer (OBC), and the science payload. Notably, the onboard computer is arguably the most critical subsystem of the CubeSat that controls the other subsystems. The OBC provides the primary programmed logic that controls the other subsystems, conducting mission-critical functionalities such as communications, data-storage, housekeeping, satellite health monitoring and payload data-collection and analysis. As such, the design of a robust, useful Flight Software (FSW) on the OBC warrants much attention in a CubeSat space mission. There are various methods in the design of CubeSat flight software, where the general methodology used involves either interrupt-based function-calls, a linear Round-Robin method, or the use of a task-scheduling operating system. In this respect, this report aims to document the overall development lifecycle of this project.